The Influence of Leadership Style and Placement on Motivation and Its Impact on the Performance of Civil Servants in the Regional Office of the National Land Agency of Jambi Province - Marlina, Fina; Zahari, M. (Dinasti Publisher, 2024)
Enhancing employee motivation and performance is crucial for effectively achieving organizational objectives. This study aims to examine the impact of leadership style and employee placement on motivation, as well as its subsequent effect on the performance of civil servants within this agency. The research employs a quantitative approach with an associative method, gathering data through questionnaires distributed to 71 employees. The data was analyzed using a structural model via the Partial Least Squares (PLS) technique. The findings indicate that both leadership style and employee placement positively and significantly influence motivation, with effects of 56.4% and 43.1%, respectively. Additionally, motivation has been shown to significantly influence employee performance by 30.8%. Leadership style and employee placement, both directly and through motivation, contribute positively to enhancing the performance of civil servants. Based on these outcomes, it is suggested that leaders at the Jambi Province Regional Office of the National Land Agency enhance collaboration with subordinates and recognize exemplary employees to further boost motivation and performance.